Self-assembly of Ni(II) porphine molecules on the Ag/Si(111)-(root 3 x root 3) R30 degrees surface studied by STM/STS and LEED - SENGE, MATHIAS (My University, 2008)
The room-temperature growth and ordering of (porphyrinato)nickel(II) (nickel(II) porphine, NiP) molecules on the Ag/Si(111)- (root 3 x root 3) R30 degrees surface have been investigated using scanning tunnelling microscopy/spectroscopy (STM/STS) and low-energy electron diffraction (LEED). The results indicate a well-ordered molecular layer in which the porphyrin molecules have a flat orientation with the molecular plane lying parallel to the substrate and forming a hexagonal overlayer on the surface. STM and LEED data obtained from one monolayer (ML) of the NiP on the Ag/Si(111)- (root 3 x root 3) R30 degrees surface show the formation of two well-ordered mirror domains, each rotated either clockwise or counterclockwise by 7? with respect to the substrate. A hexagonal Moire pattern was observed for the NiP overlayer due to long-range variation in the overlayer?substrate distance. It was found that the existence of such azimuthal rotation and the Moire pattern are caused by a lattice mismatch between the substrate and the molecular overlayer, and a corresponding model is proposed. The NiP molecules forming the second monolayer maintain the same planarity and hexagonal ordering as the first molecular layer. Scanning tunnelling spectroscopy data obtained from the NiP overlayer on the Ag/Si(111)- (root 3 x root 3) R30 degrees surface show good agreement with density functional theory calculations.
PUBLISHED
Keywords: Chemistry